Sex, Drugs and the IMF: Some Implications of "Structural Readjustment" for the Trade in Heroin, Girls and Women in the Upper Mekong Region - Feingold, David A. (Refuge: Canada’s Journal on Refugees, 1998)
A highly informed and detailed analysis of the intimate relationship between structural adjustment programs and the thriving drug and sex trade in the Upper Mekong Region of Thailand, providing additional perspective on illicit traficking and trade in the larger Southeast Asian context. Attention is specifically drawn to the harsh and disproportional impact of IMF economic policies upon women and girls, also acknowledging the great importance of and understanding of international traffic in persons, in terms of migration problems and labour exploitation, rather than solely in relation to sex.